2016
DOI: 10.1007/s13277-016-5114-y
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of ZRF1 impedes survival of estrogen receptor positive MCF-7 cells and potentiates the effect of curcumin

Abstract: The role and clinical implication of ZRF1 in breast cancer are poorly understood. So this study is aimed to explore the role of ZRF1 in breast cancer progression. With this context, we first assessed its expression pattern in FFPE primary and metastasis breast tissue samples as well as from publicly available databases. Moreover, we also explored the survival status of patients from the publicly available database and interestingly discover that high expression of ZRF1 decreases the survival of estrogen-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
6
1
Order By: Relevance
“…This observation is in agreement with a previous report describing ZRF1 as a tumor suppressor that regulates the INK4/ARF locus epigenetically and protects genomic integrity during the cell cycle [ 43 , 64 ]. However, we did not observe a similarly strong effect on cell growth in breast cancer cell lines when depleting ZRF1 compared to the dramatic growth phenotypes exhibited after ZRF1 knockdown in other cancer types [ 43 , 65 , 66 ]. Unlike for cell invasion, we noticed differences in cell proliferation and migration properties of shZRF1 cells when cultured in monolayer and in suspension.…”
Section: Discussioncontrasting
confidence: 82%
“…This observation is in agreement with a previous report describing ZRF1 as a tumor suppressor that regulates the INK4/ARF locus epigenetically and protects genomic integrity during the cell cycle [ 43 , 64 ]. However, we did not observe a similarly strong effect on cell growth in breast cancer cell lines when depleting ZRF1 compared to the dramatic growth phenotypes exhibited after ZRF1 knockdown in other cancer types [ 43 , 65 , 66 ]. Unlike for cell invasion, we noticed differences in cell proliferation and migration properties of shZRF1 cells when cultured in monolayer and in suspension.…”
Section: Discussioncontrasting
confidence: 82%
“…Focusing on the role of PRC1 in neuronal differentiation, Aloia et al identified ZRF1 as a transcriptional regulator of neural fates in embryonic stem cells [ 9 ]. Furthermore, ZRF1 expression has been associated with poor outcomes in other tumors, such as breast [ 14 , 31 ] or gastric cancer [ 15 ], thus suggesting an oncogenic role in cancer. Thus, we sought to determine whether ZRF1 plays a functional role in aggressive neuroblastomas.…”
Section: Discussionmentioning
confidence: 99%
“…Although ZRF1 is not sufficient to provide oncogenic advantages, it could still be necessary to maintain the undifferentiated and highly proliferative state of neuroblastoma cells. Previous reports demonstrated that depletion of ZRF1 resulted in a reduction of cell proliferation and the induction of apoptosis in gastric [ 15 ] or breast cancer models [ 14 ]. Conversely, Kaymak et al also showed that the reduction in cell proliferation mediated by ZRF1 depletion was accompanied by an increase in the migration and invasion properties of breast cancer cells [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA bands were observed though the gel documentation system (Bio-Rad). To further validate the DNA damage at the single-cell level, the comet assay was performed following the protocol of Rath et al 17 Briefly, the harvested cells were mixed with low-melting-point agarose, and a layer was made on an agarose-coated glass slide. The glass slides were preincubated in an alkaline lysis solution followed by electrophoresis and PI staining for 15 min.…”
Section: Determination Of Mitochondrial Membranementioning
confidence: 99%